La economía social y solidaria de la comunidad de Taquile - Montoya Canchis, Luis W. (2008)
The work approaches the relationships that the Quechua populations of the community of Taquile settle down with the tourist market, through an economic social and solidary organizational model of community type, gestated from halffilled of the years seventy, and actually it represents a conspicuous and grateful experience of social and solidary economy. Besides of presenting their antecedents and the beginning of the experience, it shows their conflicts, challenges and future perspectives.